Beyond the Discovery Void: New targets for antibacterial compounds. (1st June 2016) - Broughton, Claire; Van Den Berg, Hugo; Wemyss, Alan; Roper, David; Rodger, Alison
Antibiotics save many lives, but their efficacy is under threat: overprescription, population growth, and global travel all contribute to the rapid origination and spread of resistant strains. Exacerbating this threat is the fact that no new major classes of antibiotics have been discovered in the last 30 years: this is the "discovery void." We discuss the traditional molecular targets of antibiotics as well as putative novel targets.